What drives the 'August effect'? A observational study of the effect of junior doctor changeover on out of hours work. Issue 8 (5th July 2013) - Blakey, John D; Fearn, Andrew; Shaw, Dominick E
Objective: To investigate whether measurements of junior doctor on-call workload and performance can clarify the mechanisms underlying the increase in morbidity and mortality seen after junior doctor changeover: the 'August effect'. Design: Quantitative retrospective observational study of routinely collected data on junior doctor workload. Setting: Two large teaching hospitals in England. Participants: Task level data from a wireless out of hours system ( n  = 29, 885 requests) used by medical staff, nurses, and allied health professionals. Main outcome measures: Number and type of tasks requested by nurses, time to completion of tasks by junior doctors. Results: There was no overall change in the number of tasks requested by nurses out of hours around the August changeover (median requests per hour 15 before and 14 after, p  = 0.46). However, the number of tasks classified as urgent was greater ( p  = 0.016) equating to five more urgent tasks per day. After changeover, doctors took less time to complete tasks overall due to a reduction in time taken for routine tasks (median 74 vs. 66 min; p  = 3.9 × 10 −9 ). Conclusion: This study suggests that the 'August effect' is not due to new junior doctors completing tasks more slowly or having a greater workload. Further studies are required to investigate the causes of the increased number of urgent tasks seen, but likely factors are errors, omissions, and poor prioritization. Thus, improved training and quality control has the potential to address this increased duration of unresolved patient risk. The study also highlights the potential of newer technologies to facilitate quantitative study of clinical activity.